(untitled) («Наука и здравоохранение», 2026)
Application of the technique of conservative medical therapy in combination with the triple action of physiotherapy on the pathological focus in Peyronie’s disease compared with monotherapy in 12 patients treated by us allowed us to obtain highly effective results.